2015
DOI: 10.1007/s10661-015-5075-4
|View full text |Cite|
|
Sign up to set email alerts
|

Statistical study to identify the key factors governing ground water recharge in the watersheds of the arid Central Asia

Abstract: Understanding the source and recharge of ground waters is of great significance to our knowledge in hydrological cycles in arid environments over the world. Northern Xinjiang in northwestern China is a significant repository of information relating to the hydrological evolution and climatic changes in central Asia. In this study, two multivariate statistical techniques, hierarchical cluster analysis (HCA) and principal component analysis (PCA), were used to assess the ground water recharge and its governing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…In addition, we apply hierarchical cluster analysis of the data to group samples based on multi-elements analysis (Zhu et al, 2017). Hierarchical cluster analysis, based on Ward's method (Ward, 1963) and the Euclidean distance, was conducted to classify samples using trace elements as the variables (Wolff and Parsons, 1983;Zhu and Wang, 2016). Trace elements (Ba, Bi, Ce, Co, Cr, Cs, Ga, La, Mn, Rb, Sr, V and Zr) and Ti whose average abundance were larger than 20 ppm were selected for hierarchical cluster analysis in order to avoid errors caused by the detection limit of analytical instrument.…”
Section: Methods and Analytical Datamentioning
confidence: 99%
“…In addition, we apply hierarchical cluster analysis of the data to group samples based on multi-elements analysis (Zhu et al, 2017). Hierarchical cluster analysis, based on Ward's method (Ward, 1963) and the Euclidean distance, was conducted to classify samples using trace elements as the variables (Wolff and Parsons, 1983;Zhu and Wang, 2016). Trace elements (Ba, Bi, Ce, Co, Cr, Cs, Ga, La, Mn, Rb, Sr, V and Zr) and Ti whose average abundance were larger than 20 ppm were selected for hierarchical cluster analysis in order to avoid errors caused by the detection limit of analytical instrument.…”
Section: Methods and Analytical Datamentioning
confidence: 99%
“…Previous studies in other locations have demonstrated that factor analysis (FA) and PCA could be used for differentiation of natural and anthropogenic processes affecting groundwater chemistry (Cloutier et al 2008;Dragon and Gorski 2015;Zhu and Wang 2016;Zhu et al 2017). Anthropogenic processes such as groundwater pumping, irrigation return flow and the use of fertilizers may be influencing the groundwater composition in the study area.…”
Section: Anthropogenic Processesmentioning
confidence: 97%
“…Therefore, the hydrogeochemical evolution of groundwater in the Manas River Basin is complex due to the mutual influence of anthropogenic and natural processes. Previous studies in other locations have demonstrated that factor analysis (FA) and PCA could be used for differentiation of natural and anthropogenic processes affecting groundwater chemistry (Cloutier et al 2008;Dragon and Gorski 2015;Zhu and Wang 2016;Zhu et al 2017). Figure 5 shows the PCA scores for the first three components and the corresponding distribution of four clusters.…”
Section: Anthropogenic Processesmentioning
confidence: 99%
“…The use of N fertilizers in particular is well established throughout the world and increased use has led to extremely high NO 3 concentrations in groundwaters [47] [48] [49]. Compared with the NO 3 contents (0.5~7.7 mg/L) in the studied surface waters, groundwater samples (such as samples 16,25,26) collected from different irrigated oases in the Jungar watershed have evidently higher concentrations of NO 3 -(22-37 mg/L), indicating the strong influence of local agricultural practices in these zones.…”
Section: Irrigation Watermentioning
confidence: 99%